Etnobiologi, Etnoekologi, dan Etnoarkeologi Karawang: Sebuah Kajian Komprehensif - Ary Prihardhyanto Keim; Sahat Manaor Panggabean; Tukul Rameyo Adi; Nurul Istiqomah; Fauzi Akbar; Lady Hafidaty Rahma; Cellica Nurrachadiana; I Nyoman Lugrayasa; Nissa Arifa; Wawan Sujarwo (Journal of Tropical Ethnobiology, 2020)
The current paper is based on the result of a comprehensive study on Karawang Regency from the ethnobiological, ethnoecological, and ethnoarchaeological point of view. Being an area in the Northcoast of Java, mangrove is an integral part of the livelihood of Karawang and now is being seriously conserved. The ethnobiology and ethnoarchaeology of Karawang is astonishingly rich from the prehistoric Pleistocene to at least historical time of the Sunda Kingdom approximately from 11.000 BC to 1579 AD supported by a diversity of evidences from endemic extinct species of Bivalvia, Cardilia karawangensis to the wealthy spice ports, in which many valuable species of spices came through the port from various areas in the eastern Indonesia to the most important port of spices in Nusantara, Srivijaya Empire in Sumatera.